Leviticus 13:1-8 and The Handling of Pandemic Victims Among Priests in Nsukka, Enugu State, Nigeria - Ugwu, Collins; Eze, Virginus Uchenna; Ndukka, Ncheke Alfred; Amarachi, Ugwu Salom (Institut Agama Kristen Negeri Toraja, 2023)
Leviticus 13:1-8 presents God’s instruction to his people, Israel, on how to combat the health pandemic. The hermeneutical propagations will help the priests and church leaders fight the virus, especially among priests in Nsukka, Enugu State. According to this text, the priest is to act as a health instructor in a situation of overwhelming health challenges. It describes health challenges and the role of the priest in overcoming them. Therefore, this text can serve as a model for combating contagious diseases like Covid-19. It is on record that the emergency of the Corona virus pandemic overwhelmed the health workers. This opened a gap, which necessitated that other people, like the priests, could come in and fill it. A rhetorical-exegetical method of biblical interpretation was used. Again, observations and interviews sufficed to ascertain the extent to which the priest helped enforce precautionary measures for Covid-19 as advanced by the World Health Organization and the National Center for Disease Control. It was discovered that the priests and other ordained men of God in Nsukka, Enugu State, are not totally committed to the extra services of helping the health workers in their fight against Covid-19. This is because it does not reflect on their sermon. Also, social distancing was not observed in the churches visited, and no testing kits, not even infrared thermometers, were found in most of the churches visited. Worse still, some laity were observed entering and worshiping without a facemask and no sanction. Washing of hands with soap and use of alcohol-based hand sanitizer were noticed not to be in place in most of the remote places of worship centers that were visited. Therefore, this paper engages the priests and religious leaders within the study area to preach health protocols, provide testing materials, and establish isolation centers to assuage Covid-19 pandemic.